Pemanfaatan Serbuk Sekam Padi sebagai Katalis Basa Heterogen pada Pembuatan Biodiesel dari Minyak Kelapa - Fitriani, FBA; Togatorop, Elgrini; Lumbantoruan, Chintya Sinar (Jurnal Teknik Kimia USU, 2026)
High rice production in Indonesia generates rice husk waste of approximately 0.53–5.8 million tons in 2024, most of which has not been optimally utilized. According to the Ministry of Agriculture (2022), this waste is generally stockpiled or openly burned without further valorization. This study aims to analyze the effect of calcination temperature on the characteristics of rice husk–based heterogeneous catalysts, the effect of catalyst concentration on biodiesel yield, and the reusability of the catalyst. The results show that a calcination temperature of 600°C produces a porous catalyst with a larger number of active sites. The highest biodiesel yield of 91 mL was obtained using a catalyst concentration of 9% w/v. Catalyst reuse for up to two cycles resulted in a decrease in biodiesel yield due to the reduction of active sites; however, the yield remained above 50%. Catalyst pore characteristics were analyzed using Scanning Electron Microscopy  and the produced biodiesel met the requirements of SNI 7182:2015, including a density in the range of 850–890 kg/m³, copper strip corrosion rating of No. 2, and an acid value not exceeding 0.5 mg KOH/g.